The CCAPM meets euro-interest rate persistence, 1960-2000 - Allen C. Head; Gregor W. Smith (Queen's University, Department of Economics, 2002)
Euro-interest rates are well-known to be persistent, as are their differentials across countries for a given maturity. The international CCAPM implies that the rates are persistent because forecasts of national consumption growth or inflation are persistent too. We examine this prediction for a panel of countries. The standard CCAPM with power utility is augmented to allow for external habit, government consumption, and adaptive learning. In all cases, we find little evidence that the persistence in Euro-rates is consistent with the CCAPM.
Keywords: F30; G12; 330; Euro-interest rates; CCAPM